Functional and structural analysis of missense variants in the human PDCD1 Gene - Hanâ Baba; Meryem Bouqdayr; Anass Abbad; Asmae Saih; Benson R. Kidenya; Mohamed A. Sesay; Simpson Addo; Lahcen Wakrim; Anass Kettani (Journal of Public Health in Africa, 2025)
Background: Programmed death-1 (PD-1) is an immune checkpoint receptor that regulates T-cell function by modulating and terminating immune responses.